Autoimmune polyendocrine syndrome type 1 in an Indian cohort: a longitudinal study. Issue 5 (July 2017) - Zaidi, Ghazala; Bhatia, Vijayalakshmi; Sahoo, Saroj K; Sarangi, Aditya Narayan; Bharti, Niharika; Zhang, Li; Yu, Liping; Eriksson, Daniel; Bensing, Sophie; Kämpe, Olle; Bharani, Nisha; Yachha, Surendra Kumar; et al.
Abstract : Objective: Autoimmune polyendocrine syndrome type 1 (APS1) is a rare autosomal recessive disorder characterized by progressive organ-specific autoimmunity. There is scant information on APS1 in ethnic groups other than European Caucasians. We studied clinical aspects and autoimmune regulator ( AIRE ) gene mutations in a cohort of Indian APS1 patients. Design: Twenty-three patients (19 families) from six referral centres in India, diagnosed between 1996 and 2016, were followed for [median (range)] 4 (0.2–19) years. Methods: Clinical features, mortality, organ-specific autoantibodies and AIRE gene mutations were studied. Results: Patients varied widely in their age of presentation [3.5 (0.1–17) years] and number of clinical manifestations [5 (2–11)]. Despite genetic heterogeneity, the frequencies of the major APS1 components (mucocutaneous candidiasis: 96%; hypoparathyroidism: 91%; primary adrenal insufficiency: 55%) were similar to reports in European series. In contrast, primary hypothyroidism (23%) occurred more frequently and at an early age, while kerato-conjunctivitis, urticarial rash and autoimmune hepatitis were uncommon (9% each). Six (26%) patients died at a young age [5.8 (3–23) years] due to septicaemia, hepatic failure and adrenal/hypocalcaemic crisis from non-compliance/unexplained cause. Interferon-α and/or interleukin-22 antibodies were elevated in all 19 patients tested, including an asymptomatic infant. Eleven AIRE mutations were detected, the most common being p.C322fsX372 (haplotype frequency 37%). Four mutations were novel, while six others were previously described in European Caucasians. Conclusions: Indian APS1 patients exhibited considerable genetic heterogeneity and had highly variable clinical features. While the frequency of major manifestations was similar to that of European Caucasians, other features showed significant differences. A high mortality at a young age was observed.